Pancreatitis in Acute Lymphoblastic Leukemia - Putu Yudi Adnyani; I Nyoman Wande; Sianny Herawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Pancreatitis is inflammation of the pancreatic parenchyma and diagnosed based on symptoms of heartburn accompanied by increased levels of pancreatic enzymes. Acute pancreatitis in acute lymphoblastic leukemia in addition to being caused by therapy can also be caused by other factors. 13-year-old female patient with a diagnosis of acute lymphoblastic leukemia complained of heartburn which was felt through to the back. Patients also experience nausea, vomiting, decreased appetite, difficulty in bowel movements, and fever. Physical examination found an increase in body temperature, anemic eyes, multiple neck gland enlargement, and enlargement of the liver. The results of complete blood tests showed leukocytosis, anemia, and thrombocytopenia. The results of examination of bone marrow aspiration show a picture of the bone marrow in accordance with acute lymphoblastic leukemia (ALL-L2). Clinical chemistry tests showed an increase in amylase, lipase, SGOT, BUN, creatinine, LDH, ferritin, calcium, and procalcitonin. The patient has never received chemotherapy for the ALL. Acute pancreatitis in ALL in addition to being caused by administration of leukemia can also be caused by sepsis conditions which are complications of the ALL. ALL patients who experience acute pancreatitis in this case show a poor prognosis.